Oliver Twist - Francis, Pauline (Evans Brothers Ltd., 2007)
The story is about an orphan, Oliver Twist, who endures a miserable existence in a workhouse and then is placed with an undertaker. He escapes and travels to London where he meets the Artful Dodger, leader of a gang of juvenile pickpockets. Oliver is led to the lair of their elderly criminal trainer Fagin, naively unaware of their unlawful activities.
Keywords: Juvenile literature-Orphans-London-England-Social life ans customs-19th century-Children's stories-Fiction